Increasing drug retention in lung tissue through conjugation with polyethylene-glycol - Bayard, Fabrice J.C. (2013)
The pulmonary delivery of drugs is an attractive route of administration because of the large surface area and high permeability of the airway epithelium. The large majority of inhaled drugs are used to manage asthma and Chronic Obstructive Pulmonary Disorder (COPD), such as inhaled corticosteroids and β2-adrenergic receptor agonists. Local delivery of small molecules often results in sub-optimal pharmacokinetics characterised by short absorption times (tmax) and high systemic concentrations (Cmax). Numerous drug delivery strategies have been attempted to increase lung retention time, including drug encapsulation in microspheres, the use of polymeric excipients, or the formation of low solubility drugs. So far, drug conjugation strategies have been limited to decreasing the prodrug solubility. The non-permanent conjugation of small molecules to a large hydrophilic polymer has not been studied for pulmonary delivery. The rationale behind such a strategy is that small molecules are mainly absorbed through the epithelium by passive diffusion, the absorption rates being positively correlated to the drug lipophilicity and molecular weight. This project has therefore been looking at the production, characterisation, in vitro and ex vivo evaluation of polyethylene glycol (PEG)-ester conjugates for the sustained delivery of drugs to the lung. This thesis presents the successful oxidation and subsequent esterification of PEG of various molecular weights with prednisolone (a corticosteroid) and salbutamol (a β2-adrenergic receptor agonist). This study illustrated the feasibility of a polymeric drug conjugate strategy for sustained release of drugs to the lung. The conjugates exhibited good in vitro stability which was translated into improved pharmacokinetics and longer residence time ex vivo in the isolated and perfused rat lung. Further studies must be conducted to fully assess the role of esterases in the pulmonary hydrolysis of the conjugates and in vivo experiments would be necessary to verify the safety of the conjugates and efficacy of the drug.